Model of operational search prediction of intentional homicide by criminal police - Хижняк, Євген Сергійович; Хижняк, Є. С.; Хижняк, Евгений Сергеевич; Khyzhniak, Yevhen S.; Ханькевич, Андрій Миколайович; Ханькевич, А. М.; Ханькевич, Андрей Николаевич; Khankevych, Andrii M.; Назаренко, Ігор Віталійович; Назаренко, І. В.; Назаренко, Игорь Витальевич; Nazarenko, Ihor V.; et al. (Editorial Primmate S. A. S., 2021)
The purpose of the article is to determine the model of operational search prediction of intentional homicide by criminal police of Ukraine. Subject of research: The subject of research is a model of operational search prediction of intentional homicides by criminal police of Ukraine. Methodology: The methodological basis for the article is general and special methods and techniques of scientific knowledge, in particular: normative and dogmatic method, epistemological method, monographic method, comparative and legal method, modeling method, method of grouping, logical and legal method, method of generalization. Research results: The characteristic of the method of prediction and its use by the bodies of criminal police is given. Practical consequences: The features of the process of construction of operational search model of a situation are considered. International experience of regulating the issue under consideration is studied. Value / originality: Based on the examination of international experience, it is proposed to apply appropriate measures to combat intentional homicide in the activities of the National Police of Ukraine.

Метою статті є визначення моделі оперативно-розшукового прогнозування умисних вбивств підрозділами кримінальної поліції. Предмет дослідження: Предметом дослідження є модель оперативно-розшукового прогнозування умисних вбивств підрозділами кримінальної поліції. Методологія: Методологічною основою статті є загальні та спеціальні методи та прийоми наукового пізнання, зокрема: нормативно-догматичний метод, гносеологічний метод, монографічний метод, порівняльно-правовий метод, метод моделювання, метод групування, логіко-правовий метод, метод узагальнення. Результати дослідження: Надано характеристику методу моделювання при його використанні органами кримінальної поліції. Практичні наслідки: Розглянуто особливості процесу побудови оперативно-розшукової моделі ситуації. Вивчено міжнародний досвід регулювання досліджуваного питання. Цінність / оригінальність: На основі вивчення міжнародного досвіду запропоновано застосування відповідних заходів протидії умисним вбивствам в діяльності Національної поліції України.
Khyzhniak Ye. Model of operational search prediction of intentional homicide by criminal police / Ye. Khyzhniak, A. Khankevych, I. Nazarenko, O. Pleskach, O. Tretiak // Amazonia Investiga. – Vol. 10. - Issue 40. – Editorial Primmate S. A. S., 2021. – P. 37-44.
Keywords: model; operational search prediction; intentional homicides; National Police; international experience; модель; оперативно-розшукове прогнозування; умисне вбивство; Національна поліція; міжнародний досвід; Research Subject Categories::LAW/JURISPRUDENCE